2013
DOI: 10.3758/s13423-013-0410-7
|View full text |Cite
|
Sign up to set email alerts
|

On the automaticity of contingent capture: disruption caused by the attentional blink

Abstract: Converging evidence has shown that onset capture can be completely eliminated by the demands of a concurrent task and during the attentional blink. In the present study, we investigated contingent capture during the attentional blink. We found that contingent capture was attenuated, or even completely eliminated, during the "blink" time of the attentional blink. These results indicate that contingent capture requires limited attentional resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This was further confirmed by several recent findings [10,11]. Furthermore, Du and Abrams found that the benefit of the exogenous cue was reduced if the cue was presented within 100-200 ms after T1, when the attentional blink would be strongest, but it recovered as the interval between T1 and the cue increased [12][13][14]. Thus, the attentional blink provide a perfect measure of attentional switch characteristics.…”
Section: Introductionsupporting
confidence: 69%
“…This was further confirmed by several recent findings [10,11]. Furthermore, Du and Abrams found that the benefit of the exogenous cue was reduced if the cue was presented within 100-200 ms after T1, when the attentional blink would be strongest, but it recovered as the interval between T1 and the cue increased [12][13][14]. Thus, the attentional blink provide a perfect measure of attentional switch characteristics.…”
Section: Introductionsupporting
confidence: 69%
“…Further evidence supporting the idea that contingent capture may also involve a central bottleneck is provided by the observation that the N2pc component elicited by target-colored distractors was reduced when participants undertook a concurrent auditory task, which taxed central resources (Brisson et al, 2009). Moreover, it was recently reported that contingent capture is reduced or eliminated during the attentional blink (Du et al, 2013), suggesting that both phenomena depend on capacity-limited central resources. The notion that contingent capture involves such central resources can also account for the impairment we observed in auditory detection following the target-colored distractor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, capture is most likely when the irrelevant stimulus is physically salient (Joseph & Optican, 1996;Pashler, 1988;Theeuwes, 1991), extremely surprising (Asplund, Todd, Snyder, Gilbert, & Marois, 2010;Horstmann, 2002), signals the presence of a new perceptual object , or if it enjoys some level of top-down prioritization (Folk, Remington, & Johnston, 1992;Wolfe, 1994). However, of greatest relevance to the current study, there is also evidence that capture depends on the availability of attentional resources, with it being most likely if some amount of resources remains untapped by one's central preoccupation (Du, Yang, Yin, Zhang, & Abrams, 2013;Santangelo & Spence, 2008). For example, capture can be eliminated if spare resources are occupied with a secondary task (Boot, Brockmole, & Simons, 2005;Santangelo, Olivetti Belardinelli, & Spence, 2007) or if attentional resources are fully "frozen" within the confines of an attentional blink (Du & Abrams, 2009).…”
Section: Introductionmentioning
confidence: 72%